Design and development of a Randai-based animated learning video to enhance vocational students’ creativity through Minangkabau local wisdom - Karmila Suryani; Ade Fitri Rahmadani; Rini Widyastuti; Inna Kholidasari; Popi Fauziati; Rama Alda Prayoga; Yulcherlina Yulcherlina (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2024)
This study aims to design and develop an animated learning video integrating Randai, a traditional performing art rooted in Minangkabau local wisdom, as a culturally responsive learning medium to foster creativity among vocational students. In response to the limited use of innovative and culturally contextualized media in environmental ethics learning, this research employs a Research and Development (R&D) method using the 4D model: Define, Design, Develop, and Disseminate. During the Define stage, a needs analysis was conducted to align the video content with environmental impact materials. In the Design stage, a narrative script based on Randai was created, followed by the development of storyboards and video production using Powtoon. Expert validation was carried out in the Develop stage, and product testing involving vocational students occurred in the Disseminate phase. Research instruments included validation sheets, practicality questionnaires, and creativity assessments. Data were analyzed descriptively using percentage calculations. The results show that the developed animation video is considered valid by experts (89%) and highly practical by students (88%). Moreover, it significantly enhances students’ creative thinking skills, particularly in fluency, flexibility, and originality. This study contributes to the field by demonstrating how local cultural heritage can be effectively integrated into digital learning media, supporting the development of 21st-century skills while promoting cultural preservation in vocational education contexts.